Can the neutrophil count from hepatic fine‐needle aspirate cytology be used to diagnose hepatitis in dogs? A pilot study. (10th March 2022) - Gardner, Rachel Helen; Castillo, Daniel; Constantino‐Casas, Fernando; Williams, Tim L.
Abstract: Background: The cytologic diagnosis of inflammation on canine hepatic aspirates can be confounded by neutrophilic infiltrates in the liver of dogs with nodular regeneration, by extramedullary hematopoiesis, and by marked blood contamination. Objectives: We aimed to assess the association between neutrophil counts on hepatic cytology and the histopathologic diagnosis in dogs with hepatitis and non‐inflammatory hepatopathy. We also sought to determine a cut‐off value for the cytologic diagnosis of hepatitis. Methods: In a retrospective blinded pilot study, three observers independently reviewed hepatic aspirates that had corresponding histopathologic examinations performed within 2 days. The number of neutrophils per 200 hepatocytes was determined and averaged among observers. Only neutrophils within or directly in contact with a cluster of ≥5 hepatocytes were counted, and only intact hepatocytes within an approximate monolayer were included. Data are presented as the median (range), and the Mann‐Whitney U test is used to make comparisons between groups. Results: Eighteen cases were included (13 hepatitis and five vacuolar hepatopathy). Aspirates with a histopathologic diagnosis of hepatitis had increased numbers of neutrophils compared with those of vacuolar hepatopathy (7.7 [0.3‐18.3] vs 3.0 [1.0‐5.3]; P  = .038). Receiver operating characteristic curve analysis indicated that ≥6 neutrophils were 61.5% (CI 31.6%‐86.1%) sensitive and 100% (CI 47.8%‐100%) specific for identifying hepatitis. Conclusions: Liver aspirates from hepatitis cases have a higher number of neutrophils on cytology compared with those from vacuolar hepatopathy; however, larger studies, including those with dogs with other liver pathologies, are required. Identification of six or more neutrophils per 200 hepatocytes is highly suggestive of hepatitis.